Acquired Infection and Antimicrobial Utilization During Initial NICU Hospitalization in Infants With Congenital Diaphragmatic Hernia. Issue 5 (May 2018) - Keene, Sarah; Murthy, Karna; Pallotto, Eugenia; Brozanski, Beverly; Gien, Jason; Zaniletti, Isabella; Hulbert, Cheryl; Seabrook, Ruth; Rintoul, Natalie; Chicoine, Louis; Porta, Nicolas; Grover, Theresa R.
Abstract : Background: In addition to substantial medical and surgical intervention, neonates with congenital diaphragmatic hernia often have concurrent concerns for acquired infection. However, few studies focus on infection and corresponding antimicrobial utilization in this population. Methods: The Children's Hospital Neonatal Database was queried for congenital diaphragmatic hernia infants hospitalized from January 2010 to February 2016. Patient charts were linked to the Pediatric Health Information Systems database. Descriptive clinical data including delivery history, cultures sent, diagnosed infection, antimicrobial use and outcomes were reported. Results: A total of 1085 unique patients were identified after data linkages; 275 (25.3%) were born at <37 weeks' gestation. Bacteremia at delivery (2/1085) and in the first 7 days of life (8/1085) was less common than later infection, but 976 patients (89.9%) were treated with antibiotics. Median number of days on antibiotics was 6 [3, 11] for those without a documented infection and 21 [13, 36] for those with positive cultures. Incidence of urinary tract infection, bacteremia and pneumonia increased significantly over time and was most common after 28 days. Antibiotic use, conversely, decreased over time (92% of infants in week 1 to 44% in week 4 and beyond). Conclusions: Although culture positivity increased with age, risk of these selected infections was relatively low for a population in neonatal intensive care unit. An important mismatch is observed between culture negativity and high rates of antibiotic utilization. These data identify opportunities for antibiotic stewardship quality improvement programs.